2006
DOI: 10.1145/1111322.1111336
|View full text |Cite
|
Sign up to set email alerts
|

Why flow-completion time is the right metric for congestion control

Abstract: Abstract-Users typically want their flows to complete as quickly as possible: They want a web-page to download quickly, or a file transfer to complete as rapidly as possible. In other words, Flow Completion Time (FCT) is an important -arguably the most important -performance metric for the user. Yet research on congestion control focuses almost entirely on maximizing flow throughput, link utilization and fairness, which matter more to the operator than the user. In this paper we show that existing (TCP Reno) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
147
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 259 publications
(152 citation statements)
references
References 12 publications
0
147
0
1
Order By: Relevance
“…Moreover, our simulations have revealed that the behavior of the loss-resilience system is not sensitive to the actual value of the retransmission timeout. 3 Hence, we conclude that defining the retransmission timeout as a roughly proportional but larger version of the recovery timeout prevents unstable behavior of the system. At the same time, it permits efficient recovery of multiple losses of the same packet.…”
Section: Retransmission Based On a Timermentioning
confidence: 75%
See 1 more Smart Citation
“…Moreover, our simulations have revealed that the behavior of the loss-resilience system is not sensitive to the actual value of the retransmission timeout. 3 Hence, we conclude that defining the retransmission timeout as a roughly proportional but larger version of the recovery timeout prevents unstable behavior of the system. At the same time, it permits efficient recovery of multiple losses of the same packet.…”
Section: Retransmission Based On a Timermentioning
confidence: 75%
“…Two families of approaches have been proposed to implement congestion control. Rate-based algorithms directly control the transmission rate of the connection [2,3], whilst window-based algorithms force the connection to obey a 'packet conservation' principle, which means that a new packet is not pushed into the network until an old packet leaves [4]. Typically, window control injects bursts of data into the network, whilst rate control pushes data at regular time interval so as to meet a target average rate.…”
Section: Introductionmentioning
confidence: 99%
“…The queueing state of the entire network after applying the controller (15) is now given bẏ (20) where τ l (t) denotes the time-varying delay, l = 1, ..., M ; M is the number of time-varying delays in the network; A 0 , A l , B l , and B c are the system matrices that are defined as follows…”
Section: Proposed Decentralized Robust Congestion Control Strategymentioning
confidence: 99%
“…Motivated from the robust adaptive control techniques in [24], the time-varying gain k pi (t) is now designed according to the modified parameter projection method and is applied to system (20) to estimate the unknown but bounded incoming traffic λ pi (t) as followṡ [13] is a special case of (22) when…”
Section: Proposed Decentralized Robust Congestion Control Strategymentioning
confidence: 99%
See 1 more Smart Citation